Material Critique for Touchstone 3rd Edition: on Corpus Analysis and Spoken Grammar - Entusiastik NA (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2019)
This paper analysed the use of corpus and spoken language features in the English Language Teaching (ELT) coursebook “Touchstone”. The corpus analysis was carried out by using the British National Corpus (BNC) which was chosen for its easy and free access. In doing the spoken language analysis, I refer to McCarthy and Carter’s (2015, p.5) argument which take the grammar of conversation as ‘the benchmark for a grammar of speaking’ by considering features such as ellipsis, heads and teailsm lexical bundles, and vagueness. The analysis indicated that the language used in this coursebook signified a certain level of authentic and natural language, although areas of improvement were also found.